KAPASITAS KELEMBAGAAN DALAM PENGELOLAAN SAMPAH DI KABUPATEN PEMALANG - Aliefatul Hidayah, Aninda; Sunu Astuti, Retno; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2024)
Law Number 18 of 2008 mandates the implementation of waste management to each region through the role of regional institutions. Pemalang Regency is one of the areas with the largest waste generation in Central Java and continues to increase in line with the increase in the population. The 2021-2026 Pemalang Regency DLH Strategic Plan states that the institutional capacity of waste management is not optimal because problems arise, namely limited human resources and infrastructure. This study aims to analyze institutional capacity in waste management in Pemalang Regency and identify supporting and inhibiting factors for capacity. This research looks at institutional capacity through elements such as organizational skills, human resources, and infrastructure. Meanwhile, the supporting and inhibiting factors are joint commitment, leadership, regulations, and institutions. The method used in this study is a descriptive qualitative method. Data collection techniques are carried out through interviews and documentation. The results of the study show that the institutional capacity in managing waste in Pemalang Regency has not met the good elements of organizational skills, human resources, and infrastructure. The factors that support institutional capacity are conducive leadership, the existence of regulating regulations, and a well-established work culture climate. Meanwhile, what is an obstacle is that institutional actors have not all been involved in supporting the success of waste management.